Analysis of Factors Affecting the Selection of Sharia Hotels by Tourists in Malang - Nazwa Shafira Halwa Syah Putri; Syifaa Belvania; Natasya Adelia (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract Indonesia has a competitive edge in the tourism sector, as evidenced by the increase in the number of tourists visiting Indonesia from 2020 to 2022. This growth needs to be accompanied by improvements in supporting facilities and infrastructure, crucial components of the tourism sector, such as the hospitality industry. Profit is the primary goal in business, leading to some hotels overlooking religious values and norms. This research aims to analyze the characteristics of tourists who choose Sharia-compliant hotel services in Malang City and explore the factors influencing their decisions. The research methodology employs Structural Equation Modeling for Partial Least Squares (SEM PLS). The results indicate a positive and significant relationship between attitude, subjective norms, religiosity, normative belief towards intention, and normative belief and intention towards tourist preferences. Additionally, the variable of behavior control perspective towards intention has a negative and non-significant relationship. Keywords: SEM PLS, Sharia Hotel, TPB.